2010
DOI: 10.21273/horttech.20.5.867
|View full text |Cite
|
Sign up to set email alerts
|

Sand Topdressing Applications Improve Shear Strength and Turfgrass Density on Trafficked Athletic Fields

Abstract: Drain tile installation into a native-soil athletic field and subsequent sand topdressing applications are cost-effective alternatives to complete field renovation. However, if cumulative topdressing rates exceed root system development, surface stability may be compromised. The objective of this research was to evaluate the effects of cumulative topdressing, over a compacted sandy loam soil, on the fall wear tolerance and surface shear strength of a kentucky bluegrass (Poa pratensis Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…These findings suggest that recommendations for sand root‐zone selection, whether it be those provided by the USGA (28), ASTM (1,2), or Henderson et al (13), should be taken into consideration when selecting a cost‐effective sand topdressing material. Similar to research conducted by Kowalewski et al (15, 16), results also suggest that the benefits of sand topdressing increase when applications are repeated annually.…”
Section: Suggestions For Field Managerssupporting
confidence: 86%
See 1 more Smart Citation
“…These findings suggest that recommendations for sand root‐zone selection, whether it be those provided by the USGA (28), ASTM (1,2), or Henderson et al (13), should be taken into consideration when selecting a cost‐effective sand topdressing material. Similar to research conducted by Kowalewski et al (15, 16), results also suggest that the benefits of sand topdressing increase when applications are repeated annually.…”
Section: Suggestions For Field Managerssupporting
confidence: 86%
“…Sand topdressing has been used to develop a sand profile on golf course putting greens for over thirty years (6), and sand‐based athletic fields have been shown to provide a high‐quality athletic field on a worldwide level (5,17,23). Sand topdressing provides a number of advantages to a playing surface, including increased turfgrass density (16), cover (4,31), rooting (18), and shear strength (4,5,16,18,27). Research has also shown that sand topdressing can be used to improve surface drainage and decrease surface water runoff (15), which are important factors when trying to provide a relatively dry, stable playing surface.…”
Section: Introductionmentioning
confidence: 99%
“…Athletic field research has also shown that sand topdressing can be used to improve the characteristic of the playing surface. For instance, Kowalewski et al (2010) determined that a 1.3-cm topdressing depth applied during a 5-week period in the summer will provide improved shoot density and surface shear strength in the subsequent fall. Miller (2008) observed increased surface shear strength, percent cover, and rooting in bermudagrass [Cynodon dactylon (L.) Pers.]…”
mentioning
confidence: 99%
“…Increased sand topdressing minimized the loss of density and uniformity that occurred in lower N and lower mowing plots. Additionally, greater topdressing lessened symptoms of scalping injury that appeared at times and negatively affected turf quality in plots mowed at 2.3 m. Several studies have reported that sand topdressing maintained density under traffic, while nontopdressed plots lost density (Baker et al, 2007; Miller, 2008; Kowalewski et al, 2010). McCarty et al (2007) and White and Dickens (1984) observed that sand topdressing reduced scalping of creeping bentgrass and bermudagrass [ Cynodon dactylon (L.) Pers.…”
Section: Resultsmentioning
confidence: 99%